2020
DOI: 10.1016/j.neucom.2019.12.044
|View full text |Cite
|
Sign up to set email alerts
|

The expressivity and training of deep neural networks: Toward the edge of chaos?

Abstract: Expressivity is one of the most significant issues in assessing neural networks. In this paper, we provide a quantitative analysis of the expressivity for the deep neural network (DNN) from its dynamic model, where the Hilbert space is employed to analyze the convergence and criticality. We study the feature mapping of several widely used activation functions obtained by Hermite polynomials, and find sharp declines or even saddle points in the feature space, which stagnate the information transfer in DNNs. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the simple attention task, we observed local chaotic dynamics in SM-RC. Chaotic dynamics are of interest in deep-learning research because they increase the expressiveness of learning models [45,46]. Recently, Inoue et al observed transient chaos in transformer models [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the simple attention task, we observed local chaotic dynamics in SM-RC. Chaotic dynamics are of interest in deep-learning research because they increase the expressiveness of learning models [45,46]. Recently, Inoue et al observed transient chaos in transformer models [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the simple attention task, we observed local chaotic dynamics in SM-RC. Chaotic dynamics are of interest in deep-learning research because they increase the expressiveness of learning models [46,47]. Recently, Inoue et al observed transient chaos in transformer models [48].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of extended criticality was developed further from the concept of edge of chaos [42,147,148], which under the context of biology refers to the phenomenon that the biotic systems are in a diachronic evolving process in regions of the state space that is between chaos and equilibrium. The concept that a DNN computes at edge of chaos is not novel, and existing works [149][150][151][152] have interpreted the training of DNNs as such. Here, although the relationship between circuitsymmetry breaking and edge of chaos has not been discussed before, the discussion is mostly to clarify the criticality in the symmetry-breaking of DNNs.…”
Section: Discussion: Complexity From Adaptive-symmetries Breakingmentioning
confidence: 99%